A high-performance water-soluble sacrificial material for preparing a self-supporting film and its preparation method and application
By using Sr4Al2O7 as the sacrificial layer, the problems of poor universality of the sacrificial layer and low cleanliness and poor integrity of the self-supporting film materials in the prior art are solved, and the preparation of high-performance self-supporting oxide films is realized, providing support for the development of flexible multifunctional electronic devices.
Patent Information
- Application Number
- CN202311507798.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-09
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-11-09
AI Technical Summary
The existing sacrificial layer has poor universality and low cleanliness and poor integrity of the produced self-supporting film materials.
Sr4Al2O7 is used as a high-performance water-soluble sacrificial material. By using SrCO3 and Al2O3 as the initial raw materials, the ingredients are mixed, ground, pre-calcined and sintered according to a specific molar mass ratio, and a single crystal film of Sr4Al2O7 is formed by pulsed laser deposition. It is used as a sacrificial layer to prepare a self-supporting oxide film.
It has achieved the preparation of high integrity self-supporting oxide films with performance comparable to epitaxial films, providing a broad platform for the development of next-generation flexible multifunctional electronic devices.
Smart Images

Figure CN117534099B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of transition metal oxide thin films, and mainly to a high-performance water-soluble sacrificial material for preparing a self-supporting thin film, and a preparation method and application thereof. Background Art
[0002] The widespread electron correlation in transition metal oxides leads to strong coupling of multiple degrees of freedom such as charge, orbit, spin, and lattice, forming a rich array of ordered phases, such as ferromagnetism, ferroelectricity, and superconductivity. At the same time, the strong correlation effect allows this type of quantum material to respond extremely sensitively to external fields such as heat, electricity, magnetism, and force, which can not only achieve artificial control of physical properties, but also induce the generation of new quantum states, bringing new opportunities for the development of multifunctional electronic devices. However, the strong covalent bond formed between the oxide film and the rigid substrate greatly limits the integration with other low-dimensional materials, thereby limiting potential device applications.
[0003] In recent years, the technology of preparing self-supporting oxide films based on water-soluble sacrificial layers has developed rapidly. However, compared with traditional van der Waals materials such as graphene, the prepared self-supporting oxide films still cannot meet the requirements in terms of crystallinity and integrity. In particular, for non-ferroelectric oxide films, they are often accompanied by crystallinity degradation and high-density cracks, which in turn lead to a reduction in their physical properties, limiting their subsequent application in electronic devices. In the face of the above problems, researchers have proposed several new sacrificial layer materials to reduce the interface lattice mismatch and hinder the formation of cracks, but they are still limited by discrete lattice constants, poor solubility or poor etchant selectivity.
[0004] The Chinese patent application document with publication number CN104555902A discloses a self-supporting dielectric film and a method for preparing the same. The method comprises: providing a first substrate, and sequentially forming a first and a second sacrificial layer on the first substrate; placing the first substrate and the first and the second sacrificial layer in a liquid solvent, dissolving the first sacrificial layer, so that the second sacrificial layer is separated from the first substrate and suspended in the liquid solvent; the second sacrificial layer is a self-supporting structure and can be suspended in the liquid solvent in a stretched state; providing a second substrate with a concave portion on the surface, and using the second sacrificial layer to remove the second sacrificial layer from the liquid solvent, so that the second sacrificial layer is attached to the second substrate in a stretched state; forming a dielectric film layer on the second sacrificial layer; at least removing the portion of the second sacrificial layer corresponding to the concave portion, so that the portion of the dielectric film layer corresponding to the concave portion self-supportingly covers the concave portion. The method has stable process, low cost, short cycle, high efficiency and high flexibility and operability. However, the self-supporting material prepared by this method also has the problems of low cleanliness and poor integrity. Summary of the invention
[0005] The technical problem to be solved by the present invention is how to solve the problems of poor universality of the existing sacrificial layer and low cleanliness and poor integrity of the prepared self-supporting film material.
[0006] The present invention solves the above technical problems through the following technical means:
[0007] The first aspect of the present invention provides a high-performance water-soluble sacrificial material with a molecular formula of Sr4Al2O7, unit cell parameters of a=10.94 Å, b=11.38 Å, c=26.07 Å, α=β=γ=90°.
[0008] Beneficial effects: Sr4Al2O7 film is a versatile and efficient sacrificial layer that can produce high-integrity self-supporting oxide films with performance comparable to epitaxial films, providing a broad platform for the development of next-generation flexible multifunctional electronic devices.
[0009] The second aspect of the present invention provides a method for preparing the above-mentioned high-performance water-soluble sacrificial material, comprising the following steps:
[0010] (1) SrCO3 and Al2O3 are used as the initial raw materials, and the ingredients are prepared according to the molar mass ratio of SrCO3:Al2O3 of 3:1 (Sr3Al2O6) or 4:1 (Sr4Al2O7), and then the materials are mixed, ground, pre-calcined, pressed into shape, and sintered;
[0011] (2) Using the Sr3Al2O6 or Sr4Al2O7 fired in step (1) as a target material, a pulsed laser deposition method is used to deposit Sr4Al2O7 on the surface of a single crystal substrate to form a Sr4Al2O7 single crystal thin film.
[0012] Note: Among them, the Sr3Al2O6 target material can be controlled by growth conditions so that the components sputtered to the substrate surface deviate from the original target material, and a Sr4Al2O7 film is grown.
[0013] Preferably, in step (1), the pre-calcination temperature is 900-1200°C, and the heat preservation time is 6-12 h; the sintering temperature is 1200-1500°C, and the heat preservation time is 12-24 h.
[0014] Preferably, the laser frequency in step (2) is 1-8 Hz, and the laser energy density is 0.8-3.0 J / cm 2 .
[0015] Preferably, in step (2), the temperature of the single crystal substrate is 600-800°C, and the oxygen pressure during the growth of the Sr4Al2O7 film is 10 -5 Pa~30 Pa.
[0016] Preferably, the single crystal substrate in step (2) is lanthanum aluminate (LaAlO3), neodymium gallate (NdGaO3), strontium titanate (SrTiO3), strontium tantalate aluminate [(LaAlO3) 0.3 -(SrAl 0.5 Ta 0.5 O3) 0.7 ], one of dysprosium scandate DyScO3 (DSO), potassium tantalate (KTaO3), lanthanum strontium aluminate (LaSrAlO4), and lanthanum strontium gallate (LaSrGaO4).
[0017] Preferably, in step (2), the Sr4Al2O7 single crystal film is in an orthorhombic phase.
[0018] Preferably, the thickness of the Sr4Al2O7 single crystal film in step (2) is 2 to 100 nm.
[0019] The third aspect of the present invention proposes the use of the above-mentioned high-performance water-soluble sacrificial material in the preparation of a self-supporting film.
[0020] Preferably, the method comprises the following steps:
[0021] 1) Using the target oxide as the target material, a pulsed laser deposition method is used to perform a second deposition on the surface of the Sr4Al2O7 single crystal film to form a target oxide single crystal film;
[0022] 2) Soak the oxide film in deionized water, so that the Sr4Al2O7 sacrificial layer is completely dissolved by the deionized water at room temperature, and the target oxide film is released by peeling.
[0023] Preferably, the target oxide is NdNiO3, LaNiO3, La 0.7 Ca 0.3 MnO3、La 0.7 Sr 0.3 MnO3, SrTiO3, SrRuO3, BaTiO3, SrSnO3 and BaSnO3.
[0024] The advantages of the present invention are:
[0025] 1. The selective etchant for the Sr4Al2O7 sacrificial layer prepared by the present invention is water, which is suitable for the preparation of most self-supporting oxide films.
[0026] 2. The Sr4Al2O7 prepared by the present invention has a strong interface bonding energy with perovskite and is more easily deformed under mismatch strain, thereby adapting to a wider range of unit cell parameters.
[0027] 3. The coherent epitaxial growth of ABO3 / Sr4Al2O7 heterojunction inhibits the formation of cracks in the target oxide film during the peel-transfer peeling process. The crack-free area of the obtained non-ferroelectric self-supporting film can reach millimeter size, and the physical properties of the film are comparable to those of epitaxial films.
[0028] 4. The Sr4Al2O7 prepared by the present invention has high water solubility and can significantly improve the oxide film stripping process, which is necessary for the subsequent industrial production of large-area self-supporting films. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram of the crystal structure of a high-performance Sr4Al2O7 water-soluble sacrificial material involved in the present invention.
[0030] Figure 2 The X-ray diffraction 2θ-ω diagrams and inverse space diagrams of Sr4Al2O7 films grown on different substrates are used to characterize the epitaxial growth of Sr4Al2O7 sacrificial layers on different substrates.
[0031] Figure 3 This is an optical microscope photograph of in-situ monitoring of the process of releasing the SrTiO3 film from the substrate using the Sr4Al2O7 film as a sacrificial layer in Example 1 of the present invention; the dark area represents the hydrolyzed Sr4Al2O7 layer, and the SrTiO3 has been peeled off from the substrate, while the bright area is the part of the SrTiO3 that has not been peeled off.
[0032] Figure 4 These are the X-ray diffraction results of the SrTiO3 / Sr4Al2O7 / STO(001) heterojunction and the transferred SrTiO3 film in Example 1 of the present invention, and the optical microscope photograph of the prepared self-supporting SrTiO3 film.
[0033] Figure 5 These are the X-ray diffraction results of the SrRuO3 / Sr4Al2O7 / STO(001) heterojunction and the transferred SrRuO3 film in the embodiment of the present invention, and the optical microscope photos of the prepared self-supporting SrRuO3 film.
[0034] Figure 6 The results are the characterization results of the magnetic (MT) and electrical transport properties (ρ-T) of the SrRuO3 / Sr4Al2O7 / STO(001) heterojunction and the transferred SrRuO3 film in the embodiment of the present invention. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Embodiment 1:
[0037] A method for preparing a high-performance water-soluble sacrificial material comprises the following steps:
[0038] (1) SrCO3 and Al2O3 were used as the initial raw materials, and the ingredients were prepared according to the sacrificial layer molecular formula Sr3Al2O6 (SrCO3:Al2O3 molar mass ratio was 3:1), and then mixed, ground, pre-calcined at high temperature for three times, pressed into shape, and finally sintered. The pre-calcination temperature was 1000 °C, the holding time was 12 h, and the final sintering temperature was 1400 °C, and the holding time was 24 h.
[0039] (2) Using the Sr3Al2O6 fired in step (1) as a target, a Sr4Al2O7 single crystal thin film is formed on the surface of the STO single crystal substrate by pulsed laser deposition; the temperature of the STO substrate during the pulsed laser deposition process is 650°C; the deposition oxygen pressure is 5.0 Pa; the laser energy density is 1.0 J / cm 2 ; The laser frequency is 5 HZ; The deposition time is 20 min, and the thickness of the prepared Sr4Al2O7 is 30 nm.
[0040] The preparation of a self-supporting SrTiO3 thin film using the Sr4Al2O7 single crystal thin film prepared in this embodiment includes the following steps:
[0041] 1) Using the target oxide SrTiO3 as the target material, pulsed laser deposition was used to perform a second deposition on the surface of the Sr4Al2O7 film to form a SrTiO3 single crystal film.
[0042] 2) Cover the surface of the prepared SrTiO3 film with PDMS and soak it in deionized water, so that the Sr4Al2O7 sacrificial layer is completely dissolved by deionized water at room temperature, thereby peeling off and releasing the SrTiO3 film.
[0043] The prepared SrTiO3 film with PDMS as the support layer is transferred to single crystal silicon or other substrates for testing its physical properties.
[0044] In this embodiment, the prepared Sr4Al2O7 single crystal film is in an orthorhombic phase. Figure 1The crystal structure diagram provided in this embodiment has unit cell parameters of a=10.94 Å, b=11.38 Å, c=26.07 Å, α=β=γ=90°, and the arrangement of Sr, Al, and O atoms along the
[100] ,
[010] , and
[001] directions is as follows: Figure 1 shown.
[0045] In the present invention, the thickness of the Sr4Al2O7 sacrificial layer is 2-100 nm.
[0046] After the first deposition, the prepared Sr4Al2O7 sacrificial layer was subjected to a reciprocal space measurement (RSM) test. The test results are shown in Figure 2 As shown, it can be seen that the Sr4Al2O7 sacrificial layer and the STO (001) substrate are in an epitaxial relationship and are subjected to biaxial strain of the substrate.
[0047] The process of SrTiO3 film peeling off from the substrate was monitored in situ. The dissolution degree of the sample after being immersed in deionized water changed with time. Figure 3 As shown, the 2×2 mm sample was completely dissolved within 3.5 min.
[0048] X-ray diffraction tests were performed on the SrTiO3 / Sr4Al2O7 / STO (001) heterojunction prepared in this example and the transferred SrTiO3 / PDMS single crystal film, and the integrity of the self-supporting SrTiO3 film was characterized.
[0049] The results are as follows Figure 4 As shown: The crystallinity of the self-supporting SrTiO3 film prepared with Sr4Al2O7 as the sacrificial layer is comparable to that of the epitaxial film, and even Laue oscillations are retained, and the film integrity can reach the millimeter level.
[0050] Embodiment 2:
[0051] A method for preparing a high-performance water-soluble sacrificial material comprises the following steps:
[0052] (1) SrCO3 and Al2O3 are used as the initial raw materials, and the ingredients are prepared according to the sacrificial layer molecular formula Sr3Al2O6 (SrCO3:Al2O3 molar mass ratio is 3:1), and then mixed, ground, pre-calcined at high temperature for multiple times, pressed into shape, and finally sintered. The pre-calcination temperature is 900 ℃, the holding time is 12 h, and the final sintering temperature is 1400 ℃, and the holding time is 12 h.
[0053] (2) Using the Sr3Al2O6 fired in step (1) as a target material, a Sr4Al2O7 single crystal thin film is formed on the surface of the STO single crystal substrate by pulsed laser deposition. During the pulsed laser deposition of the Sr4Al2O7 thin film, the temperature of the STO substrate is 600 °C; the deposition oxygen pressure is 3.0 Pa; the laser energy density is 1.0 J / cm 2 ; The laser frequency is 3 HZ; The deposition time is 10 min, and the thickness of the prepared Sr4Al2O7 is 20nm.
[0054] The preparation of a self-supporting SrRuO3 thin film using the Sr4Al2O7 single crystal thin film prepared in this embodiment includes the following steps:
[0055] 1) Using the target oxide SrRuO3 as the target material, pulsed laser deposition was used to perform a second deposition on the surface of the Sr4Al2O7 film to form a SrRuO3 single crystal film.
[0056] 2) Cover the surface of the prepared SrRuO3 film with PDMS and soak it in deionized water, so that the Sr4Al2O7 sacrificial layer is completely dissolved by deionized water at room temperature, thereby peeling off and releasing the self-supporting SrRuO3 film.
[0057] The prepared SrRuO3 film with PDMS support layer is transferred to single crystal silicon or other substrates for physical property testing.
[0058] In the present invention, the crystal plane orientation of the STO single crystal substrate is preferably in the (001) direction, the Sr4Al2O7 sacrificial layer is in an orthorhombic phase, and the thickness is preferably 5 to 50 nm.
[0059] X-ray diffraction tests were performed on the SrRuO3 / Sr4Al2O7 / STO (001) heterojunction prepared in this example and the transferred PDMS / SrRuO3 single crystal film, and the integrity of the self-supporting SrRuO3 film was characterized.
[0060] The results are as follows Figure 5 As shown: The self-supporting SrRuO3 film prepared with Sr4Al2O7 as the sacrificial layer has good crystallinity, comparable to that of the epitaxial film, and its integrity can reach the millimeter level.
[0061] The magnetic (MT) and electrical transport properties (ρ-T) of the SrRuO3 / Sr4Al2O7 / STO (001) heterojunction and the transferred Si / SrRuO3 film prepared in this example were characterized. Figure 6 As shown: The physical properties of the free-standing SrRuO3 film prepared using Sr4Al2O7 as a sacrificial layer are comparable to those of epitaxial films.
[0062] Embodiment 3:
[0063] A method for preparing a high-performance water-soluble sacrificial material comprises the following steps:
[0064] (1) SrCO3 and Al2O3 are used as the initial raw materials, and the ingredients are prepared according to the sacrificial layer molecular formula Sr4Al2O7 (SrCO3:Al2O3 molar mass ratio is 4:1), and then mixed, ground, pre-calcined at high temperature for multiple times, pressed into shape, and finally sintered. The pre-calcination temperature is 1000℃, the holding time is 12 hours, and the final sintering temperature is 1300℃, and the holding time is 24 hours.
[0065] (2) Using the Sr4Al2O7 fired in step (1) as a target material, a pulsed laser deposition method is used to form a Sr4Al2O7 single crystal thin film on the surface of the STO single crystal substrate; the temperature of the STO substrate during the pulsed laser deposition of the Sr4Al2O7 thin film is preferably 700°C; the deposition oxygen pressure is 10 -2 Pa; laser energy density is 2.0 J / cm 2 ; The laser frequency is 5 HZ; The deposition time is 3 min, and the thickness of the prepared Sr4Al2O7 is 20 nm.
[0066] The preparation of a self-supporting SrTiO3 thin film using the Sr4Al2O7 single crystal thin film prepared in this embodiment includes the following steps:
[0067] 1) Using the target oxide SrTiO3 as the target material, pulsed laser deposition was used to perform a second deposition on the surface of the Sr4Al2O7 film to form a SrTiO3 single crystal film.
[0068] 2) The prepared film is immersed in deionized water, so that the Sr4Al2O7 sacrificial layer is completely dissolved by the deionized water at room temperature, thereby peeling off and releasing the self-supporting SrTiO3 film.
[0069] The performance of the Sr4Al2O7 single crystal film and the self-supporting SrTiO3 film prepared in this embodiment is similar to that in Example 1.
[0070] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high-performance water-soluble sacrificial material, characterized in that: The following steps are involved: (1) SrCO3 and Al2O3 are used as initial raw materials, and the materials are prepared according to a molar mass ratio of SrCO3:Al2O3 of 3:1 or 4:1, and then mixed, ground, pre-calcined, pressed into shape, and sintered; The pre-calcination temperature is 900~1200℃, and the heat preservation time is 6~12 hours. The sintering temperature is 1200~1500℃, and the heat preservation time is 12~24 hours. (2) Using the Sr3Al2O6 or Sr4Al2O7 sintered in step (1) as a target material, a pulsed laser deposition method is used to deposit on the surface of a single crystal substrate to form a Sr4Al2O7 single crystal film; the Sr4Al2O7 single crystal film is an orthorhombic phase; the laser frequency is 1-8 Hz, and the laser energy density is 0.8-3.0 J / cm 2 .
2. The preparation method according to claim 1, characterized in that: In the step (1), the pre-calcination temperature is 1000°C and the temperature is kept for 12 h, and the sintering temperature is 1400°C and the temperature is kept for 24 h.
3. The preparation method according to claim 1, characterized in that: The laser frequency in step (2) is 5 Hz and the laser energy density is 1.0 J / cm 2 .
4. The preparation method according to claim 1, characterized in that: In the step (2), the temperature of the single crystal substrate is 600-800°C.
5. The preparation method according to claim 1, characterized in that: The single crystal substrate in step (2) is LaAlO3, NdGaO3, SrTiO3, [(LaAlO3) 0.3 -(SrAl 0.5 Ta 0.5 O3) 0.7 ], one of DyScO3, KTaO3, LaSrAlO4, LaSrGaO4.
6. The preparation method according to claim 1, characterized in that: The thickness of the Sr4Al2O7 single crystal film in step (2) is 2 to 100 nm.
7. A high performance water-soluble sacrificial material, characterized in that: The molecular formula of the material is Sr4Al2O7, the unit cell parameters are a=10.94 Å, b=11.38 Å, c=26.07 Å, α=β=γ=90°, and the crystal phase structure of the material is an orthorhombic phase; the high-performance water-soluble sacrificial material is prepared by the preparation method described in any one of claims 1 to 6.
8. Use of the high-performance water-soluble sacrificial material according to claim 7 in the preparation of a self-supporting film.
9. The use according to claim 8, characterized in that: The following steps are involved: 1) Using the target oxide as the target material, a pulsed laser deposition method is used to perform a second deposition on the surface of the Sr4Al2O7 single crystal film to form a target oxide single crystal film; 2) Soak the film in deionized water so that the Sr4Al2O7 sacrificial layer is completely dissolved by the deionized water at room temperature, and the target oxide film is released by peeling.
10. The use according to claim 9, characterized in that: The following steps are involved: The target oxide is NdNiO3, LaNiO3, La 0.7 Ca 0.3 MnO3、La 0.7 Sr 0.3 MnO3, SrTiO3, SrRuO3, BaTiO3, SrSnO3 and BaSnO3.
Citation Information
Patent Citations
Self-supporting dielectric film and preparation method thereof
CN104555902A
Flexible bendable piezoelectric oxide film and preparation method and application thereof
CN115623851A
Preparation method for thin-film capacitor, and thin-film capacitor
WO2022040987A1